I'adah al-Nadzr (Reconsideration): A Critical Comparative Study between Indonesian Law and Saudi Arabian Law Perspectives (Fiqh Murafa’at) - Haq, Islamul; Muliati, Muliati; Amiruddin, Muhammad Majdy; Maddolangeng, Nur Misyuari; Hammad, Hamza Abed Al Karim (Institut Agama Islam Negeri Curup, 2022)
The purpose of this study was to ascertain the murafa’at fiqh (Saudi Arabian Law) and the Indonesian Criminal Procedure Code's perspectives on a convict's plea for i’adah al-nadzr (reconsideration). This was a normative juridical inquiry, which entailed poring over relevant material to gather data, assess content, and draw similarities between positive law and Islamic criminal law. The findings of this study indicated that review in positive law, referred to in Saudi Arabia's murafa’at fiqh as i’adah al-nadzr/al-muhakamah, attempted to ensure legal justice and judge justice in their rulings. There were parallels between positive law and murafa’at fiqh in terms of the justifications for filing reconsideration. There were, however, distinctions regarding the giyabi case as a basis for submitting reconsideration. In Saudi Arabia's murafa’at fiqh, the reconsideration application in the giyaby case could be accepted, although positive law did not cite the giyaby ruling as a reason to seek reconsideration. Positive law, on the other hand, provides for the possibility of resistance (verzet) if the defendant was not present in court and has not protested Verstek's ruling. Another parallel between positive law and Saudi fiqh murafa’at was seen in the reconsideration application regulations, which prohibited suspending the execution of rulings. However, the researcher notes that this rule cannot be applied universally.